PENGARUH PEMBERIAN KOMBINASI REBUSAN BIJI ALPUKAT (PERSEA AMERICANA) DAN BIJI PEPAYA (CARICA PAPAYA) TERHADAP KADAR GLUKOSA DARAH MENCIT - SHOLIHAH, ALFIATUS (Universitas Negeri Surabaya, 2013)
It has been done a research about the administrationof  decoction of avocado seeds (Persea americana), papaya seeds (Carica papaya) and a combination of both which aimed to decrease blood glucose levels in mice were given Dextrose monohydrate. Thirty mice were divided into 6 groups. Each group was given treatments namely: K1 (aquades), K2 (avocado seeds 100%), K3 (papaya seeds 100%), P1 (combine 40%), P2 (combine 50%) and P3 (combine 60%),  as much as 1 ml/20 g BW. Furthermore, all groups of mice were given Dextrose monohydrate 40% as much as 0,5 mL/20 g BW. Recorded data were level of fasting  blood glucose, 30 minutes post-treatment blood glucose levels, and post-Dextrose blood glucose levels. The results showed that administration of decoction combination of avocado seeds and papaya seeds can decrease blood glucose levels of mice with a Fhit 2,520 > Ftab 1.63 with p < 0.05. The lowest levels of blood glucose in mice are resulted from the administration of avocado seeds decoction treatment.   Key words: avocado seeds; papaya seeds; blood glucose levels